Human capital development and its impact on firm performance: Evidence from developmental economics - Maran, Marimuthu; Arokiasamy, Lawrence; Ismail, Maimunah (The Journal of International Social Research, 2009)
Human capital is getting wider attention with increasing globalization and also the saturation of the job market due to the recent downturn in the various economies of the world. Developed and developing countries put emphases on a more human capital development towards accelerating the economic growth by devoting necessary time and efforts. Thus human capital development is one of the fundamental solutions to enter the international arena. Specifically, firms must invest necessary resources in developing human capital which tend to have a great impact on performance. This paper examines the extent to which human capitals have direct impacts on firm performance from various critical perspectives. Firm performance is viewed in terms of financial and non-financial performance. Finally, this paper develops a model that explains the relationship between human capital and firm performance.